Benign Intracranial Lesions - Radiotherapy: An Overview of Treatment Options, Indications and Therapeutic Results - Tzikoulis, Vasileios; Gkantaifi, Areti; Alongi, Filippo; Tsoukalas, Nikolaos; Saraireh, Haytham H.; Charalampakis, Nikolaos; Tzikoulis, Georgios; Andreou, Emmanouil; Tsapakidis, Konstantinos; Kardamakis, Dimitrios; Tsanadis, Konstantinos; Kyrgias, George; et al. (Reviews on Recent Clinical Trials, 2020)
Background: Radiation Therapy (RT) is an established treatment option for benign intracranial lesions. The aim of this study is to display an update on the role of RT concerning the most frequent benign brain lesions and tumors. Methods: Published articles about RT and meningiomas, Vestibular Schwannomas (VSs), Pituitary Adenomas (PAs), Arteriovenous Malformations (AVMs) and craniopharyngiomas were reviewed and extracted data were used. Results: In meningiomas RT is applied as an adjuvant therapy, in case of patientrefusing surgery or in unresectable tumors. The available techniques are External Beam RT (EBRT) and stereotactic ones such as Stereotactic Radiosurgery (SRS), Fractionated Stereotactic RT (FSRT), Intensity Modulated RT (IMRT) and proton-beam therapy. The same indications are considered in PAs, in which SRS and FSRT achieve excellent tumor control rate (92-100%), acceptable hormone remission rates (>50%) and decreased Adverse Radiation Effects (AREs). Upon tumor growth or neurological deterioration, RT emerges as alone or adjuvant treatment against VSs, with SRS, FSRT, EBRT or protonbeam therapy presenting excellent tumor control growth (>90%), facial nerve (84-100%), trigeminal nerve (74-99%) and hearing (>50%) preservation. SRS poses an effective treatment modality of certain AVMs, demonstrating a 3-year obliteration rate of 80%. Lastly, a combination of microsurgery and RT presents equal local control and 5-year survival rate (>90%) but improved toxicity profile compared to total resection in case of craniopharyngiomas. Conclusion: RT comprises an effective treatment modality of benign brain and intracranial lesions. By minimizing its AREs with optimal use, RT projects as a potent tool against such diseases.
Keywords: lesions